Chemical tuning of spin clock transitions in molecular monomers based on nuclear spin-free Ni(ii). Issue 14 (3rd March 2021) - Rubín-Osanz, Marcos; Lambert, François; Shao, Feng; Rivière, Eric; Guillot, Régis; Suaud, Nicolas; Guihéry, Nathalie; Zueco, David; Barra, Anne-Laure; Mallah, Talal; Luis, Fernando
Abstract : We have directly monitored spin level anti-crossings, or "clock transitions", in Ni(ii ) molecular monomers and shown that the quantum tunnelling gap admits a chemical tuning. Abstract : We report the existence of a sizeable quantum tunnelling splitting between the two lowest electronic spin levels of mononuclear Ni complexes. The level anti-crossing, or magnetic "clock transition", associated with this gap has been directly monitored by heat capacity experiments. The comparison of these results with those obtained for a Co derivative, for which tunnelling is forbidden by symmetry, shows that the clock transition leads to an effective suppression of intermolecular spin–spin interactions. In addition, we show that the quantum tunnelling splitting admits a chemical tuning via the modification of the ligand shell that determines the crystal field and the magnetic anisotropy. These properties are crucial to realize model spin qubits that combine the necessary resilience against decoherence, a proper interfacing with other qubits and with the control circuitry and the ability to initialize them by cooling.